Influence of dental chair backrest inclination on the registration of the mandibular position - Coelho, Mariana Freire; Cavalcanti, Bruno das Neves [UNESP]; Neves, Ana Christina Claro; Jóias, Renata Pilli [UNESP]; Rode, Sigmar de Mello [UNESP] (Elsevier B. V., 2015)
Varying the inclination of the dental chair backrest might alter the distribution of occlusal contact points. The purpose of this study was to identify the influence of backrest inclination on the registration of the mandibular position. Ten participants aged between 18 and 30 years with a complete permanent dentition, uncompromised motor function, no tooth mobility, and no temporomandibular disorders were selected. To register interocclusal contacts, an autopolymerizing methylmethacrylate device was adapted to the maxillary anterior teeth and a composite resin increment was added to the mandibular central incisors. Contacts were registered with the following variations in the inclination of the dental chair backrest: 90 degrees, 120 degrees, and 180 degrees. A standardized digital photograph was made of each mark in each backrest position, and the images were superimposed to measure the distances in registration from 90 to 120 and from 90 to 180 degrees. Data were analyzed with the Student paired t test (α=.05). When the chair was inclined from the 90-degree to the 120-degree position, the mandible was repositioned posteriorly by a mean of 0.67 mm, but the difference was not statistically significant. When the chair was inclined from the 90-degree to the 180-degree position, however, the mandible was repositioned posteriorly by a statistically significant mean of 1.41 mm. Mandibular position is influenced by increasing inclination, and this influence was statistically significant at a 180-degree incline.